The growth pattern and nutrient uptake of durian (Duric zibethirius Murr.) on an oxtsol - Yaacob, Othman (Taylor & Francis, 1983)
The growth pattern and element uptake during early years of production of durian (Dicrio zvbethinuB Murr.) was studied using various ages of trees growing at Serdang, Malaysia. Growth was rapid until the seventh year when the dry matter production was nearly at its maximum. The proportion of underground to above ground materials decreases as the tree ages and in a seven-year old tree, 30% is roots and 70% tops. The elements (N, P, K, Ca and Mg) stored in the vegetative parts increases with the age of the tree in a similar manner to that of the total dry matter. However, the amount of elements stored in a seven-year old tree exceeds that which was applied as fertilizers suggesting that the once-jungle tree obtains additional elements from the soil. The element removed in fruits during the first two years of production was low. In general, the growth and early production of durian on an Oxisol, using the agronomic practices adopted at Serdang, are satisfactory.